PENGARUH THINK PAIR SHARE, MIND MAPPING DAN JIGSAW TERHADAP PEMAHAMAN KONSEP SISWA - Iskandar, Iskandar; Badruzzaman, Deden (Jurnal Riset Akuntansi dan Keuangan, 2017)
Abstract: The purpose of this study is to determine the ability of students’ conceptual understanding by applying cooperative learning models through Think Pair Share, Mind Mapping, and Jigsaw. The method used Quasi Experiment with Counterbalanced Design. This study takes a sample from class XI Office Administration consisted of 114 students from 3 classes. Each class was an experimental class and each treatment used a different model. The results of data analysis with t-test (independent samples t-test) of the confidence level 95% obtained value    and the probability value sig. (2-tailed) 0.05. Based on the results, the average value (mean) of students' conceptual understanding in each study showed that Mind Mapping always higher than Jigsaw and Think Pair Share. Therefore, Mind Mapping is more effective in improving students' conceptual understanding skills in the subject of Administration of Facilities and Infrastructure.Keywords: conceptual understanding; cooperative learning model;  jigsaw; mind mapping; think pair share. Abstrak: Tujuan penelitian ini adalah untuk mengetahui kemampuan pemahaman konsep siswa dengan menerapkan model pembelajaran kooperatif, tipe Think Pair Share, Mind Mapping, dan Jigsaw. Metode yang digunakan adalah Quasi Eksperimen dengan desain penelitian Counterbalanced  Design. Penelitian ini mengambil sampel dari kelas XI Administrasi Perkantoran terdiri dari 114 siswa dari 3 kelas, dimana setiap kelasnya merupakan kelas eksperimen dan di setiap treatment menggunakan model yang berbeda. Hasil analisis data dengan uji t (independent samples t-test) pada taraf kepercayaan 95% diperoleh nilai     dan nilai probalitas sig. (2-tailed) 0,05. Dilihat dari hasil perolehan nilai rata-rata (mean) kemampuan pemahaman konsep siswa disetiap studi, bahwa tipe Mind Mapping selalu lebih tinggi daripada Jigsaw dan Think Pair Share. Jadi, model pembelajaran kooperatif tipe Mind Mapping lebih efektif dalam meningkatkan kemampuan pemahaman konsep siswa pada mata pelajaran Administrasi Sarana dan Prasarana.Kata kunci: jigsaw; mind mapping; model pembelajaran kooperatif; pemahaman konsep; think pair share.